A música como instrumento de aprendizagem de língua inglesa no ensino regular - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2023)
The main focus of this study was to address the contribution of using music as a pedagogical tool for learning English in Educação Básica schools, an educational context still empirically stigmatized as unfavorable for the success of language learning, especially if we consider the public school system. Through a literature review based on texts from authors as Vera Lúcia P. Bréscia, David Crystal, Violeta Hemsy de Gainza, among others, we sought to demonstrate the comprehensive potential of using music in English classes, beyond its purpose of linguistic competence, in the construction of critical-reflexive subjects with historical and cultural knowledge, capable of understanding, acting, and transforming the world around them, with the mediation of better prepared teachers, conscious of their fundamental role in this process.
Keywords: Música na educação; Ensino de língua inglesa; Formação de professores; Prática pedagógica; CNPQ::LINGUISTICA, LETRAS E ARTES::LETRAS; ODS 4 – Educação de qualidade; ODS 10 – Redução das desigualdades